Bromerade flamskyddsmedel (PBDE) i fisk och sediment – en litteraturstudie och en fallstudie av tio svenska referenssjöar - Kvernes, Eva (2020)
Flame retardants are used in plastics, fabrics, furnishing foam and electronics to reduce their fire hazards. The kind of brominated flame retardants presented in this study are the PBDEs, polybrominated diphenyl ethers. Because their molecular structures are similar to PCBs, there is a fear that these substances are environmental hazards as the PCBs, by decreasing the thyroid hormone levels. Lower brominated PBDEs are found to cause deterioration of memory capacity, learning capability, and motoric behaviour. There is a discussion going on whether the higher brominated PBDEs have the same effect. During the last decades the level of PBDEs in the environment has increased. Two cases that have drawn much attention to the PBDEs are the discoveries of PBDEs in eggs of peregrine falcon (Falco peregrinus) and in breast milk in Swedish women.